2017
DOI: 10.1074/mcp.m116.063503
|View full text |Cite
|
Sign up to set email alerts
|

Label-free Proteomic Analysis of Exosomes Derived from Inducible Hepatitis B Virus-Replicating HepAD38 Cell Line

Abstract: Hepatitis B virus (HBV) infection is a major health problem worldwide. Recent evidence suggests that some viruses can manipulate the infection process by packing specific viral and cellular components into exosomes, small nanometer-sized (30-150 nm) vesicles secreted from various cells. However, the impact of HBV replication on the content of exosomes produced by hepatocytes has not been fully delineated. In this work, an HBV-inducible cell line HepAD38 was used to directly compare changes in the protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 62 publications
4
56
0
Order By: Relevance
“…The molecular basis of 19S RP sorting within exosomes will have to be more accurately defined, together with the fact that part of intracellular 19S RP might also be released another pathway than exosomes. Very interestingly, a study recently reported that hepatitis B virus replication modulates exosome content, in particular with an enhancement of subunits of the 19S RP It is thus tempting to speculate that HBV replication induces a cellular stress which in some way activates a signaling cascade leading to the same effect as serum starvation described here.…”
Section: Discussionsupporting
confidence: 52%
“…The molecular basis of 19S RP sorting within exosomes will have to be more accurately defined, together with the fact that part of intracellular 19S RP might also be released another pathway than exosomes. Very interestingly, a study recently reported that hepatitis B virus replication modulates exosome content, in particular with an enhancement of subunits of the 19S RP It is thus tempting to speculate that HBV replication induces a cellular stress which in some way activates a signaling cascade leading to the same effect as serum starvation described here.…”
Section: Discussionsupporting
confidence: 52%
“…exosomes. This is well illustrated by Yuan and colleagues in their study of exosome composition upon infection with the important human pathogen, hepatitis B virus (10). Interestingly, exosomes contained proteasome subunits that were further shown to have the ability to regulate host immune responses.…”
mentioning
confidence: 74%
“…The increase in these miRNAs potentially inhibit NK cell activity via IL-12 downregulation and facilitating viral evasion of the host immune response [ 56 ]. Another study concluded through proteomic analysis of exosomes via LC-MS/MS that HBV-infected HepAD38 hepatoblastoma cell line-derived exosomes contain HBV-associated proteins capable of significantly reducing monocyte IL-6 production [ 58 ]. HBV infection in HepAD38 cells alters 35 exosome-bound proteins, including the increase of five proteasome subunit proteins: PSMD1, PSMD7, PSMD14, PSMC1, and PSMC2, enhancing proteolytic activity [ 58 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%
“…Another study concluded through proteomic analysis of exosomes via LC-MS/MS that HBV-infected HepAD38 hepatoblastoma cell line-derived exosomes contain HBV-associated proteins capable of significantly reducing monocyte IL-6 production [ 58 ]. HBV infection in HepAD38 cells alters 35 exosome-bound proteins, including the increase of five proteasome subunit proteins: PSMD1, PSMD7, PSMD14, PSMC1, and PSMC2, enhancing proteolytic activity [ 58 ]. Inhibition of exosome-dependent proteasomal activity resulted in increased IL-6 production, implying proinflammatory molecules modulated by proteasomal subunit proteins within HepAD38 exosome transport [ 58 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%